2009
DOI: 10.1037/a0016530
|View full text |Cite
|
Sign up to set email alerts
|

Initial construction and validation of the Pathological Narcissism Inventory.

Abstract: The construct of narcissism is inconsistently defined across clinical theory, social-personality psychology, and psychiatric diagnosis. Two problems were identified that impede integration of research and clinical findings regarding narcissistic personality pathology: (a) ambiguity regarding the assessment of pathological narcissism vs. normal narcissism and (b) insufficient scope of existing narcissism measures. Four studies are presented documenting the initial derivation and validation of the Pathological N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

92
1,303
5
44

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,074 publications
(1,494 citation statements)
references
References 102 publications
92
1,303
5
44
Order By: Relevance
“…In recent years, the distinction between grandiose and vulnerable narcissism has received increasing attention (Miller et al, 2011;Pincus et al, 2009;Pincus & Lukowitsky, 2010). Research suggests that the NPI, which has been used in five of the six studies included in the present research, captures mostly grandiose aspects of narcissism Maxwell, Donnellan, Hopwood, Personality Questionnaire for Children-Revised (Ang & Raine, 2009) suggests that the same holds for the measure used in the sixth study.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…In recent years, the distinction between grandiose and vulnerable narcissism has received increasing attention (Miller et al, 2011;Pincus et al, 2009;Pincus & Lukowitsky, 2010). Research suggests that the NPI, which has been used in five of the six studies included in the present research, captures mostly grandiose aspects of narcissism Maxwell, Donnellan, Hopwood, Personality Questionnaire for Children-Revised (Ang & Raine, 2009) suggests that the same holds for the measure used in the sixth study.…”
Section: Limitations and Future Directionsmentioning
confidence: 73%
“…On the basis of Wink's (1991) results, Hendin and Cheek (1997) developed the HSNS (Hendin & Cheek, 1997) specifically to measure vulnerable narcissism, thus the HSNS was assigned to the vulnerable category, as was a single study that used the Dutch Narcissism Scale (DNS; Ettema & Zondag, 2002; i.e., we coded the DNS Vulnerable Narcissism subscale, which is based on the HSNS, as a measure of vulnerable narcissism). The PNI (Pincus et al, 2009) was also explicitly developed to measure vulnerable narcissism, but in addition to the vulnerable content, the PNI has a Grandiose subscale. The PNI Grandiose subscale was coded as grandiose (DSM-NPI) narcissism, and the PNI Vulnerable subscale was coded as vulnerable narcissism (the Grandiose and Vulnerable PNI subscales were based on the PNI second-order factors provided by Wright, Lukowitsky, Pincus, & Conroy, 2010).…”
Section: Codingmentioning
confidence: 99%
“…Results in Table 6 lend support to our choice of factors to represent the three narcissism facets because all of the alternative measures of L/A, G/E, and E/E were correlated (r > .70) with Ackerman et al's (2011) three facets. Finally, for the sake of completeness, in addition to the Ackerman et al (2011) three facets of narcissism, we separately calculated meta-analytic facet (Raskin & Terry, 1988); NPI-16 = 16 item NPI (Ames, Rose, & Anderson, 2006); HDS-Bold = Hogan Development Survey (Hogan & Hogan, 1997;; CPI = California Personality Inventory (Gough&Bradley, 1996); Dirty Dozen = Dirty Dozen (Jonason&Webster, 2010); APSD = Antisocial Process Screening Device (Frick et al, 2000); PNI = Pathological Narcissism Inventory (Pincus et al, 2009); PDQ-4 = Personality Diagnostic Questionnaire-4 (Hyler, 1994); SCID = Structured Clinical Interview for DSM-IV Personality Disorders (First et al, 1997); NGS = Narcissistic Grandiosity Scale (Rosenthal, Hooley, & Steshenko, 2007); NARQ = Narcissistic Admiration and Rivalry Questionnaire (Back et al, 2013); SD3 = Short Dark Triad (Jones & Paulhus, 2014); MMPI = Minnesota Multiphasic Personality Inventory; MCMI = Millon Clinical Multiaxial Inventory (Millon, Millon, Davis, & Grossman, 2006b); IPDE = International Personality Disorders Examination (Loranger, 1999); OMNI = O'Brien Multiphasic Narcissism Inventory (O'Brien, 1987); NESARC = National Epidemiological Survey on Alcohol and Related Conditions; AHNS = Add Health Narcissism Study (Davis & Brunell, 2012); SNAP-2 = Schedule for Nonadaptive and Adaptive Personality (Clark, 1993); NPQC-R = Narcissistic Personality Questionnaire for Children-Revised (Ang & Raine, 2009); SQ = The Schema Questionnaire (Young, 1990); SIDP-IV = Structured Interview for DSM-IV Personality (Pfohl, Blum, & Zimmerman, 1997); DIPD-IV = The Diagnostic Interview for DSM-IV personality disorders (Zanarini, Frankenburg, Sickel, & Yong, 1996); Selfism Scale (Phares & Erksine, 1984); CNS = Childhood Narcissism Scale (Thomaes, Stegge, Bushman, Olthof, & Denissen, 2008); NEO-PI-R = NEO Personality Inventory-Revised (Miller, Lyman, Widiger, & Leukefeld, 2001); DNS = Dutch Narcissis...…”
Section: Codingmentioning
confidence: 99%
“…Previous research has found small negative connections with stress-related traits such as neuroticism (Jones and Paulhus 2010;Jones and Weiser 2014;Paulhus and Williams 2002). Former studies also suggest that narcissism should be considered in two forms (grandiose and vulnerable), and that Neuroticism may be a key in differing between the two (Miller et al 2011;Pincus et al 2009). The importance of studying dark personalities as well as normal personalities is that traits may be considered a foundation to how people generally view everyday life (Jones and Paulhus 2013).…”
Section: Dark Triadmentioning
confidence: 99%